2016
DOI: 10.1002/lary.26008
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging improves observer reliability in evaluation of upper aerodigestive tract lesions

Abstract: 4 Laryngoscope, 126:2276-2281, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
3
23
0
2
Order By: Relevance
“…Between August 2012 and December 2014, 370 endoscopies of the upper aerodigestive tract were performed using both conventional WLI and NBI at the Department of Otorhinolaryngology of the University Medical Center Groningen, the Netherlands. Endoscopic procedures were performed according to standard protocol under general anaesthesia, using an Olympus HD camera head with a 0°, 5.4‐mm telescope and Evis Exera CLV‐180 light source (Olympus BV, Zoeterwoude, the Netherlands) . Patient data and images were stored in the electronic patient records and analysed retrospectively.…”
Section: Methodssupporting
confidence: 90%
“…Between August 2012 and December 2014, 370 endoscopies of the upper aerodigestive tract were performed using both conventional WLI and NBI at the Department of Otorhinolaryngology of the University Medical Center Groningen, the Netherlands. Endoscopic procedures were performed according to standard protocol under general anaesthesia, using an Olympus HD camera head with a 0°, 5.4‐mm telescope and Evis Exera CLV‐180 light source (Olympus BV, Zoeterwoude, the Netherlands) . Patient data and images were stored in the electronic patient records and analysed retrospectively.…”
Section: Methodssupporting
confidence: 90%
“…The epithelial infectious stimulus in recurrent respiratory papillomatosis causes neoangiogenesis in a similar way, but fortunately, these viral lesions are usually fairly easily recognizable for the clinician due to their typical appearance . Evaluation of the vasculature in laryngeal and hypopharyngeal lesions by NBI has been shown to increase the observer reliability compared to white light examination alone …”
Section: Discussionmentioning
confidence: 99%
“…Especially in patients without clinical suspicion of severe disease, it is often considered unethical to perform a biopsy, and therefore it is impossible to obtain a histopathological evaluation for comparison. A general limitation of the available literature is the concurrent use of white light endoscopy, which may influence the diagnostic accuracy, as stated by Cosway et al Other recognized limitations are the inadequate reports of specific data, an unequivocal use of histopathological terms and classification, and last but not least, an uneven definition of what constitutes test‐positive results …”
Section: Discussionmentioning
confidence: 99%
“…Since the first studies with NBI by Muto et al, the number of NBI studies in head and neck cancer has been growing rapidly. Many reports show that NBI is superior to white‐light imaging (WLI) in detection of head and neck squamous cell cancer . A recent study showed that NBI is helpful in accurately determining the extent of laser surgery in laryngeal cancer and, therefore, reduces the number of positive surgical magins …”
Section: Introductionmentioning
confidence: 99%
“…Many reports show that NBI is superior to white-light imaging (WLI) in detection of head and neck squamous cell cancer. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][19][20][21] A recent study showed that NBI is helpful in accurately determining the extent of laser surgery in laryngeal cancer and, therefore, reduces the number of positive surgical magins. 22 Until now, no studies have been performed to establish the prognostic role of NBI-assisted endoscopy in combination with laser excision of early glottic cancer.…”
Section: Introductionmentioning
confidence: 99%